Lithofacies and age of the Quintuco Formation (Lower Cretaceous) in the Mallín Quemado area (Sierra de la Vaca Muerta, Neuquén Basin, Argentina). Stratigraphic and depositional implications - Garrido, Alberto C. (2017)
Fil: A.C. Garrido - Museo Provincial de Ciencias Naturales “Prof. Dr. Juan A. Olsacher”, Dirección Provincial de Minería, Etcheluz y Ejército Argentino, 8340 Zapala, Neuquén, Argentina & Departamento Geología y Petróleo, Facultad de Ingeniería, Universidad Nacional del Comahue, Buenos Aires 1400, 8300 Neuquén, Argentina